The equity-financing channel, the catering channel, and corporate investment: International evidence - KUSNADI, Yuanto (Institutional Knowledge at Singapore Management University, 2017)
We examine how stock market mispricing affectscorporate investment in an international setting. We find that investment ismore sensitive to stock prices for equity-dependent firms than for non-equity-dependentfirms in our international sample. Investment is also more sensitive to stockprices for firms located in countries with more developed capital markets (i.e.,lower costs of raising capital), higher share turnover (i.e., shortershareholder horizons), and higher R&D intensity (i.e., more opaque assets). More importantly, the positive relation between equitydependence and the sensitivity of investment to stock prices is more pronouncedfor firms located in these same countries. These findings are consistent withthe equity-financing hypothesis and the catering hypothesis on corporateinvestment proposed by Baker et al. (2003) and Polk and Sapienza (2009),respectively.